Expanding the CAR toolbox with high throughput screening strategies for CAR domain exploration: a comprehensive review - Sebastien Anguille; Eva Lion; Khloe S Gordon; Michael E Birnbaum; Gils Roex (Journal for ImmunoTherapy of Cancer)
Chimeric antigen receptor (CAR)-T-cell therapy has been highly successful in the treatment of B-cell hematological malignancies. CARs are modular synthetic molecules that can redirect immune cells towards target cells with antibody-like specificity. Despite their modularity, CARs used in the clinic are currently composed of a limited set of domains, mostly derived from IgG, CD8α, 4-1BB, CD28 and CD3ζ. The current low throughput CAR screening workflows are labor-intensive and time-consuming, and lie at the basis of the limited toolbox of CAR building blocks available. High throughput screening methods facilitate simultaneous investigation of hundreds of thousands of CAR domain combinations, allowing discovery of novel domains and increasing our understanding of how they behave in the context of a CAR. Here we review the growing body of reports that employ these high throughput screening and computational methods to advance CAR design. We summarize and highlight the important differences between the different studies and discuss their limitations and future considerations for further improvements. In conclusion, while still in its infancy, high throughput screening of CARs has the capacity to vastly expand the CAR domain toolbox and improve our understanding of CAR design. This knowledge could be foundational for translating CAR therapy beyond hematological malignancies and push the frontiers in personalized medicine.